Low α2-Plasmin Inhibitor Antigen Levels on Admission Are Associated With More Severe Stroke and Unfavorable Outcomes in Acute Ischemic Stroke Patients Treated With Intravenous Thrombolysis - Székely, Edina Gabriella; Orbán-Kálmándi, Rita; Szegedi, István; Katona, Éva; Baráth, Barbara; Czuriga-Kovács, Katalin Réka; Lóczi, Linda; Vasas, Nikolett; Fekete, István; Fekete, Klára; Berényi, Ervin; Oláh, László; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Intravenous administration of recombinant tissue plasminogen activator (rt-PA) fails to succeed in a subset of acute ischemic stroke (AIS) patients, while in approximately 6–8% of cases intracerebral hemorrhage (ICH) occurs as side effect. Objective Here, we aimed to investigate α2-plasmin inhibitor (α2-PI) levels during thrombolysis and to find out whether they predict therapy outcomes in AIS patients. Patients/Methods In this prospective, observational study, blood samples of 421 AIS patients, all undergoing i.v. thrombolysis by rt-PA within 4.5 h of their symptom onset, were taken before and 24 h after thrombolysis. In a subset of patients (n = 131), blood was also obtained immediately post-lysis. α2-PI activity and antigen levels were measured by chromogenic assay and an in-house ELISA detecting all forms of α2-PI. α2-PI Arg6Trp polymorphism was identified in all patients. Stroke severity was determined by NIHSS on admission and day 7. Therapy-associated ICH was classified according to ECASSII. Long-term outcomes were defined at 3 months post-event by the modified Rankin Scale (mRS). Results Median α2-PI activity and antigen levels showed a significant drop immediately post-lysis and increased to subnormal levels at 24 h post-event. Admission α2-PI levels showed a significant negative stepwise association with stroke severity. Patients with favorable long-term outcomes (mRS 0–1) had significantly higher admission α2-PI antigen levels (median:61.6 [IQR:55.9–70.5] mg/L) as compared to patients with poor outcomes (mRS 2–5: median:59.7 [IQR:54.5–69.1] and mRS 6: median:56.0 [IQR:48.5–61.0] mg/L, p < 0.001). In a Kaplan–Meier survival analysis, patients with an α2-PI antigen in the highest quartile on admission showed significantly better long-term survival as compared to those with α2-PI antigen in the lowest quartile (HR: 4.54; 95%CI:1.92–10.8, p < 0.001); however, in a multivariate analysis, a low admission α2-PI antigen did not prove to be an independent risk factor of poor long-term outcomes. In patients with therapy-related ICH (n = 34), admission α2-PI antigen levels were significantly, but only marginally, lower as compared to those without hemorrhage. Conclusions Low α2-PI antigen levels on admission were associated with more severe strokes and poor long-term outcomes in this cohort. Our results suggest that in case of more severe strokes, α2-PI may be involved in the limited efficacy of rt-PA thrombolysis.